The Role of E3 Ubiquitin Ligases and Deubiquitinases in Inflammatory Bowel Disease: Friend or Foe? - Zou, Min; Zeng, Qi-Shan; Nie, Jiao; Yang, Jia-Hui; Luo, Zhen-Yi; Gan, Hua-Tian (Frontiers in Immunology, 2021)
Inflammatory bowel disease (IBD), which include Crohn's disease (CD) and ulcerative colitis (UC), exhibits a complex multifactorial pathogenesis involving genetic susceptibility, imbalance of gut microbiota, mucosal immune disorder and environmental factors. Recent studies reported associations between ubiquitination and deubiquitination and the occurrence and development of inflammatory bowel disease. Ubiquitination modification, one of the most important types of post-translational modifications, is a multi-step enzymatic process involved in the regulation of various physiological processes of cells, including cell cycle progression, cell differentiation, apoptosis, and innate and adaptive immune responses. Alterations in ubiquitination and deubiquitination can lead to various diseases, including IBD. Here, we review the role of E3 ubiquitin ligases and deubiquitinases（DUBs）and their mediated ubiquitination and deubiquitination modifications in the pathogenesis of IBD. We highlight the importance of this type of posttranslational modification in the development of inflammation, and provide guidance for the future development of targeted therapeutics in IBD.